Characterization of proinsulin‐specific regulatory T cells in type 1 diabetes at different ages of onset. Issue 3 (27th January 2019) - Paul, Mahinder; Dayal, Devi; Bhansali, Anil; Sachdeva, Naresh
Abstract : Background and Objectives: Regulatory T cells (Tregs) play an important role in maintaining tolerance to self‐antigens. Defects in the frequency and function of polyclonal Tregs have been reported in type 1 diabetes (T1D). However, characteristics of proinsulin (PI)‐specific Tregs in human T1D have not yet been explored. Therefore, we aimed to characterize PI‐specific Tregs in two distinct pathophysiological subtypes of T1D, juvenile‐onset T1D (JOT1D) and adult‐onset T1D (AOT1D), distinguished by the age of onset. Methods: Peripheral blood mononuclear cells of the recruited subjects were stimulated in vitro with PI‐derived peptides. PI‐specific Tregs were characterized by flow cytometry using the combination of markers CD25, CD137, FOXP3 and CD45RA. Results: Firstly, we observed similar frequencies of polyclonal Tregs in the T1D (n = 25) and healthy control (HC) (n = 20) subjects ( P = 0.96), with a positive correlation between age and frequency of polyclonal Tregs (r = +0.35, P = 0.04). While the frequency of polyclonal Tregs was higher in AOT1D group ( P = 0.02), both JOT1D (n = 14) and AOT1D groups (n = 11) had a comparable frequency of PI‐specific Tregs in their peripheral blood. The frequency of PI‐specific memory Tregs was significantly high in both the JOT1D ( P = 0.02) and AOT1D ( P = 0.009) groups compared to their respective HC groups (n = 10). Finally, we observed no significant difference in the expression of FOXP3 and IL‐2 receptor in PI‐specific Tregs in all the groups. Conclusions: Unlike polyclonal Tregs, both T1D subtypes harbor comparable frequencies of PI‐specific Tregs. Chronic antigen presentation results in a distinct memory‐like phenotype of PI‐specific Tregs in these subjects irrespective of the age of disease onset.